Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

Crystalline xylitol production from corncob biomass with oral toxicity analysis - Ahuja, Vishal; Dasgupta, Diptarka; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; More, Snehal; Gupta, Piyush; Behera, Babita; Bhaskar, Thallada (Industrial Crops and Products, 2022)
Xylitol, a five-carbon sugar alcohol, has a steady global market and finds application as a natural sugar substitute in various food and confectionery products. Biocatalytic xylitol production, although touted as a greener alternative to conventional chemical catalysis, suffers from certain challenges, the primary being high cost of production. This study demonstrates a process for food-grade xylitol production from corncob biomass with energy reduction through two major process modifications. A non-conventional fermentation strategy was adopted whereby adjusting aeration without agitation, xylitol with high yield (0.86 +/- 0.015 g/g), and productivity (0.74 gL(-1)h(-1)) could be produced by a GRAS Pichia caribbica MTCC 5703 strain. Xylitol was recovered from the broth in the form of crystals using a combination of membrane-based filtration and crystallization. The crystals demonstrated similar to 98 % purity when quantified with H-1 NMR. Oral toxicity analysis of the crystals demonstrated no adverse effect in female Winstar rats (at a loading of 2000 mg/kg body weight of animals). Overall process statistics showed that 0.584 kg of food-grade xylitol crystals could be produced from 3.5 kg of corncob biomass. The two-process modifications during fermentation and xylitol recovery enabled an energy saving of similar to 20.842 kW/kg of crystals, providing tremendous advantages for biorefinery-based large-scale xylitol production from corncob biomass.
Keywords: Biomass; Fermentation; Oral toxicity analysis; Wastewater treatment; xylitol